Control System for a Pulsed Current Source based on Digital Hysteresis and Current Estimation - Penovi, Emiliano (2014)
This work presents the implementation of a control system for a high-precision pulsed current source. The proposed control scheme employs a digital hysteresis to achieve a well-defined precision and a high dynamic response. The existence of measurement noise, comparable with the amplitude of the hysteresis bands, generates unwanted commutations that tend to increase the power losses in the semiconductors and to reduce overall system efficiency. As a solution, a current estimation algorithm is proposed. This estimator incorporates the semiconductors state information to improve the filtering capability without affecting the measurement dynamics. Experimental results validate the proposed control scheme.